Mineralogical and Heavy Metal Assessment of Iraqi Soils from Urban and Rural Areas. - Al Derzi, Nidal; Naji, Amel Muhsen (Al-Nahrain Journal of Science, 2018)
The concentrations of Cu, Ni, Pb, Zn, and Cr in top soils (0-15 cm) from urbanized and rural areas of Iraq were measured by X-ray fluorescence analysis (XRF). The results revealed that soil samples located in urban areas had higher metal contents than did soil samples from rural areas. This was probably due to local pollution from increased population and other industrial sources.The comparison with the soil quality guidelines showed that metal concentrations in all the studied locations are lower than the permissible levels admitted by the World Health Organization (WHO).The mineralogical composition of the top soils, identified by X-ray diffraction (XRD), was predominantly Quartz, Calcite and minor minerals such as Dolomite, Feldspar and clay minerals. Total clay minerals in the soil samples, ranged from 3-10%, were found to be dominated by Montmorillonite, Kaolinite and Feldspar. The highest clay content was observed in Diala soils near the river Tigris.